Do Hospital Mergers Reduce Waiting Times? Theory and Evidence from the English NHS - Vanessa Cirulli; Giorgia Marini; Marco A. Marini; Odd Rune Straume (Fondazione Eni Enrico Mattei (FEEM), 2023)
We analyse - theoretically and empirically - the effect of hospital mergers on waiting times in healthcare markets where prices are fixed. Using a spatial modelling framework where patients choose provider based on travelling distance and waiting times, we show that the effect is theoretically ambiguous. In the presence of cost synergies, the scope for lower waiting times as a result of the merger is larger if the hospitals are more profit-oriented. This result is arguably confirmed by our empirical analysis, which is based on a conditional flexible difference-indifferences methodology applied to a long panel of data on hospital mergers in the English NHS, where we find that the effects of a merger on waiting times crucially rely on a legal status that can reasonably be linked to the degree of profit-orientation. Whereas hospital mergers involving Foundation Trusts tend to reduce waiting times, the corresponding effect of mergers involving hospitals without this legal status tends to go in the opposite direction.
Keywords: I11; I18; L21; L41; 330; Hospital merger; waiting times; profit-orientation